A tethering mechanism underlies Pin1-catalyzed proline cis–trans isomerization at a noncanonical site - Christopher C. Williams; Jonathan Chuck; Paola Munoz-Tello; Douglas J. Kojetin (Proceedings of the National Academy of Sciences, 2025)
The prolyl isomerase Pin1 catalyzes the cis – trans isomerization of proline peptide bonds, a noncovalent posttranslational modification that influences cellular and molecular processes, including protein–protein interactions. Pin1 is a two-domain enzyme containing a WW domain that recognizes phosphorylated serine/threonine-proline (pS/pT-P) canonical motifs and an enzymatic PPIase domain that catalyzes proline cis – trans isomerization of pS/pT-P motifs. Here, we show that Pin1 uses a tethering mechanism to bind and catalyze proline cis – trans isomerization of a noncanonical motif in the disordered N-terminal activation function-1 (AF-1) domain of the human nuclear receptor PPARγ. NMR reveals multiple Pin1 binding regions within the PPARγ AF-1, including a canonical motif (pS112-P113) that when phosphorylated by the kinase ERK2 binds the Pin1 WW domain with high affinity. NMR methods reveal that Pin1 also binds and accelerates cis – trans isomerization of a noncanonical motif containing a tryptophan-proline motif (W39-P40) previously shown to be involved in an interdomain interaction with the C-terminal ligand-binding domain (LBD) of PPARγ. Cellular transcription studies combined with mutagenesis and Pin1 inhibitor treatment reveal a functional role for Pin1-mediated acceleration of cis – trans isomerization of the PPARγ W39-P40 motif. Our data inform a refined model of the Pin1 catalytic mechanism where the WW domain can bind a canonical pS/T-P motif and tether Pin1 to a target, which enables the PPIase domain to exert catalytic cis – trans isomerization at a distal noncanonical site.